'Every Citizen of Empire Implored to Save the Children!' Empire, internationalism and the Save the Children Fund in inter‐war Britain1. Issue 231 (21st August 2012) - Baughan, Emily
Abstract In the immediate aftermath of the First Word War, internationalist ideals became increasingly important in British politics, popular culture and society. However, this new vogue for internationalism did not mean that imperial sentiments were waning, rather imperial celebrations such as Empire Day and the 1924 Empire Exhibition became increasingly prominent. This article explores the tensions and intersections between internationalist and imperialist world views in the activities and publications of the Save the Children Fund (S.C.F.), Britain's most successful international charity in the inter‐war years. It argues that, despite its radical, internationalist agenda, the S.C.F. was involved in a process of reimagining the British empire as a peaceable, moral force, which exemplified the co‐operative spirit of internationalism. In this vein, the S.C.F. promoted a vision of imperial international responsibility, arguing that it was the duty of the united British empire to extend its care to the children of all nations. In instances where the fund's imperial language sat uneasily with its more radical membership, a discourse of 'humanity' and universal responsibility was mobilized to overcome tensions. However, embedded within this discourse of humanity remained a hierarchical imagining of a 'world civilization', of which the British, both through their empire and their support for internationalist principles, were the champions and exemplars.